Optimization of adsorption parameters for reactive red 4 (rr4) removal by cross-linked chitosan-epichlorohydrin using boxbehnken design / Nurul Najwa Abd Malek, Emad Yousif and Ali H. Jawad - Abd Malek, Nurul Najwa; Yousif, Emad; H. Jawad, Ali (Faculty of Applied Sciences, 2020)
Cross-linked chitosan-epichlorohydrin was prepared for the adsorption of Reactive Red 4 (RR4). Response surface methodology (RSM) with 3-level Box-Behnken design (BBD) was employed to optimize the RR4 dye removal efficiency from aqueous solution. The adsorption key parameters that were selected such as adsorbent dose (A: 0.5 - 1.5 g), pH (B: 4 - 10) and time (30 - 80 min). The F-value of BBD model for RR4 removal efficiency was 185.36 (corresponding p-value < 0.0001). The results illustrated that the highest RR4 removal efficiency (70.53%) was obtained at the following conditions: adsorbent dose (1.0 g), pH 4 and time of 80 min.